Padrões de representação do estereótipo do gênero feminino na propaganda brasileira - Shinoda, Luciana Messias (2017)
This study investigates female gender stereotypes in Brazilian printed advertising, understanding advertising as a transmitter of cultural values and beliefs. A content analysis of n = 1208 advertisements published in female, male and general content magazines during the years of 1995, 2005 and 2015 was held. The investigation considered both manifested and latent aspects of the advertisements, analyzing the (1) Physical Characteristics and the (2) Gender Roles of the woman represented and the (3) Subtle Sexism associated to her in the images. These three levels of analysis, together with the Product Category, allowed the identification of thirteen 'Patterns of Representation of Female Gender Stereotype in Print Advertising'. The study indicates that, during the period of analysis, the gender roles in which women were represented have become wider while the subtle sexism showed a gradual reduction of frequency. Besides, changes on the physical characteristics and associated sexism were observed in each pattern of representation of female gender stereotype. Regarding the physical characteristics, in all three periods of analysis, a dominant physical pattern was observed: white skin, young age and slim/lean body. Therefore, the study highlights the need of wider representations in terms of physical characteristics in Brazilian print advertising.